Challenges and Opportunities in International Business Management - Idris, Muhammad; Nurhadi, Nurhadi; Sakinah, Sakinah (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the challenges and opportunities in international business management, focusing on the complex dynamics shaping organizational strategies in a global context. It aims to understand how cultural diversity, economic volatility, and geopolitical risks influence international operations and how businesses can leverage these factors for strategic advantage. Research Design and Methodology: The study employs a qualitative research design with a literature review approach. It systematically analyzes scholarly works, including academic journals, books, and reports. This method provides a comprehensive understanding of the multifaceted aspects of international business management, highlighting both challenges and opportunities. Findings and Discussion: The findings indicate that cultural diversity presents a significant challenge in international business, emphasizing the importance of cultural intelligence in navigating diverse environments. Economic volatility and geopolitical risks also require adaptive strategies to manage global uncertainties. Despite these challenges, the study identifies opportunities for growth through digital transformation and strategic collaborations, suggesting that businesses can capitalize on innovation and cross-cultural engagement for success. Implications: The study highlights the need for organizations to invest in cross-cultural competence, foster inclusive cultures, and collaborate with policymakers to address regulatory complexities. It recommends further research on the role of digital technologies and strategic alliances in enhancing global business performance, enabling organizations to achieve sustained success and competitive advantage in the international marketplace.